Social Media and Primary School Science: Examining the Impact of Tiktok on Year 5 Students' Performance in Light Energy - Roberd, Amyzee; Roslan, Roslinawati (International Journal of Social Learning (IJSL), 2022)
Using social media as an instructional option has attracted great attention. Nevertheless, little is known about how social media applications such as TikTok support student learning in science. This action research investigated the impact of TikTok lessons on students' performance in light energy. It also explored students' perceptions of using TikTok in science learning. A total of 14 conveniently sampled Year 5 students from one of the primary schools in Brunei Darussalam participated in this study. Data were collected through a pretest, post-tests, observations, and interviews and analyzed using One-way Repeated Measures ANOVA and thematic analysis. The TikTok interventions improved students' performance in light energy, with post-test higher than pretest scores. The students had a positive perception of the TikTok intervention provided. TikTok is regarded as user-friendly, and the TikTok lessons are collaborative, engaging, and fun. Implications are discussed.